Productive Measles Virus Brain Infection and Apoptosis in CD46 Transgenic Mice - Evlashev, Alexey (American Society for Microbiology, 2000)
Measles virus (MV) infection causes acute childhood disease, associated in certain cases with infection of the central nervous system (CNS) and development of neurological disease. To develop a murine model of MV-induced pathology, we generated several lines of transgenic mice ubiquitously expressing as the MV receptor a human CD46 molecule with either a Cyt1 or Cyt2 cytoplasmic tail. All transgenic lines expressed CD46 protein in the brain. Newborn transgenic mice, in contrast to nontransgenic controls, were highly sensitive to intracerebral infection by the MV Edmonston strain. Signs of clinical illness (lack of mobility, tremors, and weight loss) appeared within 5 to 7 days after infection, followed by seizures, paralysis, and death of the infected animals. Virus replication was detected in neurons from infected mice, and virus was reproducibly isolated from transgenic brain tissue. MV-induced apoptosis observed in different brain regions preceded the death of infected animals. Similar results were obtained with mice expressing either a Cyt1 or Cyt2 cytoplasmic tail, demonstrating the ability of different isoforms of CD46 to function as MV receptors in vivo. In addition, maternally transferred immunity delayed death of offspring given a lethal dose of MV. These results document a novel CD46 transgenic murine model where MV neuronal infection is associated with the production of infectious virus, similarly to progressive infectious measles encephalitis seen in immunocompromised patients, and provide a new means to study pathogenesis of MV infection in the CNS.